Direct addition of poly-lysine or poly-ethylenimine to the medium: A simple alternative to plate pre-coating. - Alexander Faussner; Matthias M Deininger; Christian Weber; Sabine Steffens (PLoS ONE, 2022)
For most cell culture experiments, it is indispensable that the cells are firmly anchored to culture plates, withstanding rinsing steps that can create shear forces and tolerating temperature changes without detaching. For semi-adherent cells such as the common HEK 293 or PC-12 cells, this could so far be obtained by time-consuming plate pre-coating with cationic polymer solutions. We report here, that i) pre-coating with the cheaper poly-ethylenimine (PEI) works as well as the commonly used poly-D-lysine (PDL), but more importantly and novel ii) that simple direct addition of either PEI (1.5 μg/ml) or PDL (2 μg/ml) to the cell culture medium results in strongly anchored HEK 293 cells, indistinguishable from ones seeded on pre-coated plates. Therefore, the replacement of plate pre-coating by direct addition of either PEI or PDL gives comparable excellent results, but is highly labour-, time-, and cost-efficient. Moreover, we could show that addition of PDL or PEI also works similarly well in animal-free culture using human platelet lysate instead of fetal bovine serum. Interestingly, additional experiments showed that strong cell attachment requires only cationic polymers but not fetal bovine serum or human platelet lysate added to the medium.